Positive Solution of a Quadratic Integral Equation Using Generalization of Darbo's Fixed Point Theorem. (27th July 2019) - Arab, Reza; Mursaleen, Mohammad; Rizvi, Syed M. H.
Abstract: The objective of this article is to establish a fixed point theorem using different class of control functions, which is a generalization of Darbo's fixed point theorem (DFPT) and its various versions obtained by several authors. Using this result we obtain existence of at least one positive solution for a quadratic integral equation of Fredholm type.